Field-Simulation Based Engineering of RF Antenna Probes with Non-Uniform Substrates for High-Field Magnetic Resonance Imaging Systems - Gandji, Navid P.; Palle, Akshay V.; Semouchkin, George B.; Semouchkina, Elena (Applied Computational Electromagnetics Society Journal (ACES), 2021)
It is proposed to replace RF volume coils in high-field Magnetic Resonance Imaging (MRI) scanners by a microstrip patch antenna system. The performed computational studies have demonstrated an opportunity to form extended 3D volumes of homogenous RF magnetic fields by using a system of placed vis-à-vis two patch antennas. In order to control antenna dimensions and homogeneity of antenna near fields, the substrates of antennas have been engineered by appropriate patterning of high permittivity dielectric inserts. A variety of antennas with engineered substrates responding at 600 MHz for application in 14T MRI scanners have been designed, and the homogeneity of magnetic fields achieved inside the antenna system has been demonstrated.